A peptide of the amino-terminus of GRK2 induces hypertrophy and yet elicits cardioprotection after pressure overload. (May 2021) - Bledzka, Kamila M.; Manaserh, Iyad H.; Grondolsky, Jessica; Pfleger, Jessica; Roy, Rajika; Gao, Erhe; Chuprun, J. Kurt; Koch, Walter J.; Schumacher, Sarah M.
Abstract: G protein-coupled receptor (GPCR) kinase 2 (GRK2) expression and activity are elevated early on in response to several forms of cardiovascular stress and are a hallmark of heart failure. Interestingly, though, in addition to its well-characterized role in regulating GPCRs, mounting evidence suggests a GRK2 "interactome" that underlies a great diversity in its functional roles. Several such GRK2 interacting partners are important for adaptive and maladaptive myocyte growth; therefore, an understanding of domain-specific interactions with signaling and regulatory molecules could lead to novel targets for heart failure therapy. Herein, we subjected transgenic mice with cardiac restricted expression of a short, amino terminal fragment of GRK2 (βARKnt) to pressure overload and found that unlike their littermate controls or previous GRK2 fragments, they exhibited an increased left ventricular wall thickness and mass prior to cardiac stress that underwent proportional hypertrophic growth to controls after acute pressure overload. Importantly, despite this enlarged heart, βARKnt mice did not undergo the expected transition to heart failure observed in controls. Further, βARKnt expression limited adverse left ventricular remodeling and increased cell survival signaling. Proteomic analysis to identify βARKnt binding partners that may underlie the improved cardiovascular phenotype uncovered a selective functional interaction of both endogenous GRK2 and βARKnt with AKT substrate of 160 kDa (AS160). AS160 has emerged as a key downstream regulator of insulin signaling, integrating physiological and metabolic cues to couple energy demand to membrane recruitment of Glut4. Our preliminary data indicate that in βARKnt mice, cardiomyocyte insulin signaling is improved during stress, with a coordinate increase in spare respiratory activity and ATP production without metabolite switching. Surprisingly, these studies also revealed a significant decrease in gonadal fat weight, equivalent to human abdominal fat, in male βARKnt mice at baseline and following cardiac stress. These data suggest that the enhanced AS160-mediated signaling in the βARKnt mice may ameliorate pathological cardiac remodeling through direct modulation of insulin signaling within cardiomyocytes, and translate these to beneficial effects on systemic metabolism. Graphical abstract: Unlabelled Image Highlights: GRK2 has a complex cardiovascular interactome. Amino and carboxyl domains of GRK2 elicit cardiprotection. Uniquely, an amino terminal portion (βARKnt) elicits physiological hypertrophy. Domain-specific protein interactions may represent therapeutic targets. An interaction with AS160 elicits enhanced metabolic signaling and performance.